A novel 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR) splice variant with an alternative exon 1 potentially encoding an extended N-terminus - Stormo, Camilla (BioMed Central, 2012)
BACKGROUND: The major rate-limiting enzyme for de novo cholesterol synthesis is 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR). HMGCR is sterically inhibited by statins, the most commonly prescribed drugs for the prevention of cardiovascular events. Alternative splicing of HMGCR has been implicated in the control of cholesterol homeostasis. The aim of this study was to identify novel alternatively spliced variants of HMGCR with potential physiological importance. RESULTS: Bioinformatic analyses predicted three novel HMGCR transcripts containing an alternative exon 1 (HMGCR-1b, -1c, -1d) compared with the canonical transcript (HMGCR-1a). The open reading frame of the HMGCR-1b transcript potentially encodes 20 additional amino acids at the N-terminus, compared with HMGCR-1a. Reverse transcription quantitative polymerase chain reaction (RT-qPCR) was used to examine the mRNA levels of HMGCR in different tissues; HMGCR-1a was the most highly expressed variant in most tissues, with the exception of the skin, esophagus, and uterine cervix, in which HMGCR-1b was the most highly expressed transcript. Atorvastatin treatment of HepG2 cells resulted in increased HMGCR-1b mRNA levels, but unaltered proximal promoter activity compared to untreated cells. In contrast, HMGCR-1c showed a more restricted transcription pattern, but was also induced by atorvastatin treatment. CONCLUSIONS: The gene encoding HMGCR uses alternative, mutually exclusive exon 1 sequences. This contributes to an increased complexity of HMGCR transcripts. Further studies are needed to investigate whether HMGCR splice variants identified in this study are physiologically functional.